A lower gender equality consciousness in rural and left-behind children: a latent class analysis - Li, Yifei; Zhang, Jingping; Zhang, Jie; Li, Juan; Chen, Yiping; Zuo, Man (Frontiers in Psychology, 2024)
Objective: School age is a critical period for the development of individual gender equality consciousness. The purpose of this study was to explore the potential classes of school-age children's gender equality consciousness, influencing factors and their differences in gender role, thus providing targeted guidance for the formulation and implementation of gender equality education strategies.A cross-sectional survey was conducted among 1846 school-age children using the demographic information questionnaire, gender equality consciousness questionnaire and Bem Sex Role Inventory. A latent class analysis was performed to explore gender equality consciousness latent classes. Multinomial logistic regression analysis was conducted to examine the predictors of class membership, and chi-square test was used to compare the gender role of each latent class.The average age of the included 1846 participants was 10.10±1.82 years old. The proportion of boy, grade 6 and living in urban area respectively were 50.8%, 25.3% and 60.2%. The only children was 16.3% and left-behind children was 22.5%. 60.5% of all children thought their parents had a good relationship. The core family structure in all participants was 54.1%. Mothers were the caregivers of most children(63.6%). The same-sex friends more than 3 was 73.5%, while opposite-sex friends ranged from 0 to 1 was 41.7%. Three latent classes were identified and labeled 'high gender equality consciousness' class (20.6%), 'moderate gender equality consciousness' class (42.3%) and 'low high gender equality consciousness' class (37.1%). Factors affecting the different types of school-age children's gender equality consciousness include gender, grade, caregiver, place of residence, whether they are left-behind children and parental relationship. Rural and left-behind children are more likely to enter the 'low gender equality consciousness' group. Children in the 'low gender equality consciousness' group had a lower proportion of androgynous gender role.Rural children and left-behind children are the priority groups for gender equality education. Gender role is the important predictors and intervention targets of children's gender equality consciousness. Educators or policy makers can formulate targeted intervention measures according to the influencing factors of potential classes.